INTEGRATION OF THEORY AND PRACTICE IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF TEACHERS OF VOCATIONAL EDUCATION - Akhadova Gulnoza (Modern American Journals, 2025)
The development of professional competence of teachers in the field of vocational education occupies a central place in education. For the effective functioning of the educational system, for the high qualification of students, competency of teachers is very important. In the development of professional competence of the teacher, the integration of theoretical foundations and practice is of particular importance. This article analyzes the theoretical and practical aspects of the development of professional competence of teachers of professional education.
Keywords: Vocational education, professional competence, theory, practice, integration, practical skills.